RIVOJLANAYOTGAN MAMLAKATLARDA RAQAMLASHTIRISHNING IQTISODIY О‘SISHGA TA’SIRI - Ergashev, Gayrat Urolovich (THE INNOVATION ECONOMY, 2025)
This paper examines the impact of digitalization on economic growth in developing countries. It analyzes key aspects, including improved access to information, growth of e-commerce, increased financial inclusion, automation of processes, and creation of new jobs. It concludes with recommendations for developing digital infrastructure, training in digital skills, and supporting innovation. The results of the study confirm that digitalization is a key factor in sustainable economic development.